Electrolyte and battery containing same
By adding sulfonylbenzothiazole compounds and oxazoleone compounds to the electrolyte of lithium-ion batteries, the problem of electrolyte decomposition of lithium-ion batteries at high temperatures is solved, and the high-temperature and low-temperature performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202311357805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-19
AI Technical Summary
Existing lithium-ion batteries can easily lead to electrolyte decomposition at high temperatures, shortening the battery's cycle life and storage performance.
By adding sulfonylbenzothiazole compounds and oxazoleone compounds to the electrolyte solution, the composition of the solid electrolyte interface mask is optimized and the high-temperature storage and circulation performance of the battery is improved.
It significantly improves the high-temperature storage performance, high-temperature cycling performance, high-temperature floating charging performance and low-temperature discharge performance of lithium-ion batteries, and extends the service life of the battery.
Smart Images

Figure BDA0004502315560000021 
Figure BDA0004502315560000031 
Figure BDA0004502315560000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to an electrolyte and a battery containing the electrolyte. Background Art
[0002] Lithium-ion batteries have been widely used as power sources in our daily lives due to their irreplaceable advantages such as low self-discharge rate, long cycle life, high operating voltage, and low pollution. Whether in mobile communications, laptops, or new energy vehicles, they have broad application prospects. At the same time, users have also put forward requirements for lithium-ion batteries such as high energy density and fast charging. In lithium-ion battery systems, the continuous increase in battery operating voltage and operating temperature will lead to different degrees of electrolyte decomposition, thereby accelerating the degradation and failure of battery performance. Summary of the invention
[0003] In order to improve the deficiencies of the prior art, the present invention provides an electrolyte and a battery containing the electrolyte. During the first charge and discharge process, the electrolyte will partially decompose, thereby forming a passivation film on the surface of the electrode material, which is called a solid electrolyte interface film (SEI film). The chemical composition and structure of the SEI film play a key role in improving the operating voltage, operating temperature and cycle life of the battery. Adding a small amount of additives to optimize the composition of the SEI film is the most economical and convenient method to improve battery performance. The electrolyte provided by the present invention utilizes the mutual cooperation of sulfonylbenzothioxazole compounds and oxazolone compounds, which can not only stabilize the quality of the electrolyte, but also have good film-forming properties. When used in batteries, the high-temperature storage performance, high-temperature cycle performance, high-temperature floating charge performance and low-temperature discharge performance of the battery can be significantly improved.
[0004] In order to achieve the above object, the present invention adopts the following technical solution:
[0005] An electrolyte comprises an organic solvent, an electrolyte salt, a first additive and a second additive; the first additive comprises a sulfonylbenzothioxazole compound, and the second additive comprises an oxazolone compound.
[0006] According to an embodiment of the present invention, the sulfonylbenzothioxazole compound is a benzothioxazole compound containing a sulfonyl group.
[0007] According to an embodiment of the present invention, the sulfonylbenzothioxazole compound includes at least one of the compounds shown in Formula I:
[0008]
[0009] Wherein, R1 is selected from hydrogen, halogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkoxy; if substituted, the substituent is alkyl or halogen; R2 is selected from halogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkoxy, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl; if substituted, the substituent is alkyl or halogen; Y is O element or S element.
[0010] According to an embodiment of the present invention, R1 is selected from halogen, substituted or unsubstituted C 1-12 Alkyl, substituted or unsubstituted C 1-12 Alkoxy; if substituted, the substituent is C 1-12 Alkyl or halogen; R2 is selected from halogen, substituted or unsubstituted C 1-12 Alkyl, substituted or unsubstituted C 2-12 Alkenyl, substituted or unsubstituted C 1-12 Alkoxy, substituted or unsubstituted C 6-12 aryl, substituted or unsubstituted 5-12 membered heteroaryl; if substituted, the substituent is C 1-12 Alkyl or halogen; Y is O element or S element.
[0011] According to an embodiment of the present invention, R1 is selected from halogen, substituted or unsubstituted C 1-6 Alkyl, substituted or unsubstituted C 1-6 Alkoxy; if substituted, the substituent is C 1-6 Alkyl or halogen; R2 is selected from halogen, substituted or unsubstituted C 1-6 Alkyl, substituted or unsubstituted C 2-6 Alkenyl, substituted or unsubstituted C 1-6 Alkoxy, substituted or unsubstituted C 6-10 aryl, substituted or unsubstituted 5-10 membered heteroaryl; if substituted, the substituent is C 1-6 Alkyl or halogen; Y is O element or S element.
[0012] According to an embodiment of the present invention, R1 is selected from halogen, substituted or unsubstituted C 1-3 Alkyl, substituted or unsubstituted C 1-3 Alkoxy; if substituted, the substituent is C 1-3 Alkyl or halogen; R2 is selected from halogen, substituted or unsubstituted C 1-3 Alkyl, substituted or unsubstituted C 2-3 Alkenyl, substituted or unsubstituted C 1-3 Alkoxy, substituted or unsubstituted C 6-8 aryl, substituted or unsubstituted 5-6 membered heteroaryl; if substituted, the substituent is C 1-3 Alkyl or halogen; Y is O element or S element.
[0013] According to an embodiment of the present invention, R1 is selected from methyl, ethyl, propyl, methoxy, trifluoromethyl or fluorine; R2 is selected from methyl, ethyl, propyl, vinyl, trifluoromethyl, thienyl or furyl.
[0014] According to an embodiment of the present invention, the first additive includes at least one of the following compounds I-1 to I-11:
[0015]
[0016] According to an embodiment of the present invention, the first additive can be purchased from commercial sources, or can be prepared by a method known in the art.
[0017] According to an embodiment of the present invention, the mass of the first additive accounts for 0.02wt% to 5wt% of the total mass of the electrolyte, preferably 0.05 to 3wt%, for example, 0.02wt%, 0.03wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% , 1.0wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt%, 2.6wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.6wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt%, 4.8wt%, 5wt% or any point in the range consisting of any two of the above points.
[0018] According to an embodiment of the present invention, the second additive comprises at least one of the compounds represented by formula II:
[0019]
[0020] Wherein, R3 is selected from substituted or unsubstituted alkyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl; if substituted, the substituent is alkoxy, alkyl or halogen.
[0021] According to an embodiment of the present invention, R3 is selected from substituted or unsubstituted C 1-12 Alkyl, substituted or unsubstituted C 6-12 aryl, substituted or unsubstituted 5-12 membered heteroaryl; if substituted, the substituent is C 1-12 Alkoxy, C 1-12 Alkyl or halogen.
[0022] According to an embodiment of the present invention, R3 is selected from substituted or unsubstituted C 1-6Alkyl, substituted or unsubstituted C 6-10 aryl, substituted or unsubstituted 5-10 membered heteroaryl; if substituted, the substituent is C 1-6 Alkoxy, C 1-6 Alkyl or halogen.
[0023] According to an embodiment of the present invention, R3 is selected from substituted or unsubstituted C 1-3 Alkyl, substituted or unsubstituted C 6-8 aryl, substituted or unsubstituted 5-6 membered heteroaryl; if substituted, the substituent is C 1-3 Alkoxy, C 1-3 Alkyl or halogen.
[0024] According to an embodiment of the present invention, R3 is selected from methyl, substituted or unsubstituted phenyl, substituted or unsubstituted thienyl; if substituted, the substituent is fluorine, trifluoromethyl or methoxy.
[0025] According to an embodiment of the present invention, the term "halogen" includes fluorine, chlorine, bromine and iodine.
[0026] According to an embodiment of the present invention, the second additive includes at least one of the following compounds II-1 to II-7:
[0027]
[0028]
[0029] According to an embodiment of the present invention, the second additive can be purchased from commercial sources, or can be prepared using a method known in the art.
[0030] According to an embodiment of the present invention, the mass of the second additive accounts for 0.1wt% to 8wt% of the total mass of the electrolyte, preferably 0.2wt% to 5wt%, for example, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%. t%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.2wt%, 2.5wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt%, 4.8wt%, 5wt%, 5.2wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt% or any point in the range consisting of any two of the above points.
[0031] According to an embodiment of the present invention, the electrolyte further includes a third additive, and the third additive includes a sultone compound.
[0032] According to an embodiment of the present invention, the sultone compound includes at least one of the compounds represented by formula III:
[0033]
[0034] Wherein, R4, R5, and R6 are the same or different and are independently selected from hydrogen, halogen, substituted or unsubstituted alkyl; if substituted, the substituent is alkyl or halogen.
[0035] According to an embodiment of the present invention, R4, R5, and R6 are the same or different and are independently selected from hydrogen, halogen, substituted or unsubstituted C 1-12 Alkyl; if substituted, the substituent is C 1-12 Alkyl or halogen.
[0036] According to an embodiment of the present invention, R4, R5, and R6 are the same or different and are independently selected from hydrogen, halogen, substituted or unsubstituted C 1-6 Alkyl; if substituted, the substituent is C 1-6 Alkyl or halogen.
[0037] According to an embodiment of the present invention, R4, R5, and R6 are the same or different and are independently selected from hydrogen, halogen, substituted or unsubstituted C 1-3 Alkyl; if substituted, the substituent is C 1-3 Alkyl or halogen.
[0038] According to an embodiment of the present invention, the sultone compound is selected from at least one of the following compounds III-1 to III-10:
[0039]
[0040] According to an embodiment of the present invention, the mass of the third additive accounts for a percentage of 0.1wt% to 10wt% of the total mass of the electrolyte, preferably 1.0wt% to 3.5wt%, for example, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt%, 4.8wt%, 5wt%, 5.2wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt% or any point value in the range composed of any two of the above point values.
[0041] According to an embodiment of the present invention, the organic solvent includes cyclic carbonate and / or chain carbonate.
[0042] Preferably, the cyclic carbonate includes at least one of ethylene carbonate and propylene carbonate.
[0043] Preferably, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate or ethyl propyl carbonate.
[0044] According to an embodiment of the present invention, the organic solvent is a cyclic carbonate and a chain carbonate.
[0045] Preferably, the mass ratio of the cyclic carbonate to the linear carbonate is 1:(2-3), such as 1:2, 1:2.2, 1:2.4, 1:2.6, 1:2.8 or 1:3. When the mass ratio of the cyclic carbonate to the linear carbonate is 1:(2-3), the electrolyte has a reasonable viscosity and conductivity, and can ensure good electrochemical performance. When the content of the cyclic carbonate is too low (such as less than 1:2), although the electrolyte viscosity is low, the conductivity is also low, the battery polarization increases, and the cycle and rate performance are poor; when the content of the cyclic carbonate is too high (such as greater than 1:3), the electrolyte viscosity increases, the battery polarization is also large, and the electrochemical performance is reduced.
[0046] According to an embodiment of the present invention, the electrolyte salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium difluorophosphate (LiPF2O2), lithium difluorobisoxalate phosphate (LiPF2(C2O4)2), lithium tetrafluorooxalate phosphate (LiPF4C2O4), lithium oxalate phosphate (LiPO2C2O4), lithium bisoxalatoborate (LiBOB), lithium difluorooxalatoborate (LiODFB), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2) and lithium bis(fluorosulfonyl)imide (LiFSI).
[0047] According to an embodiment of the present invention, the molar concentration of the electrolyte salt in the organic solvent is 1.0 to 1.5 mol / L, for example, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L or 1.5 mol / L.
[0048] According to an embodiment of the present invention, the electrolyte is used in a lithium ion battery.
[0049] The present invention also provides a method for preparing the above electrolyte, the method comprising the following steps:
[0050] The electrolyte solution is prepared by mixing an organic solvent, an electrolyte salt, a first additive, a second additive, and a third additive which may or may not be added.
[0051] According to an embodiment of the present invention, the mixing includes stirring mixing or ultrasonic mixing.
[0052] Preferably, the mixing temperature is -10°C to 25°C, such as -10°C, -5°C, 0°C, 5°C, 10°C or 15°C.
[0053] The present invention also provides a battery, comprising the above-mentioned electrolyte.
[0054] According to an embodiment of the present invention, the battery is a lithium-ion battery.
[0055] According to an embodiment of the present invention, the battery further includes a positive electrode sheet, a negative electrode sheet and a separator.
[0056] According to an embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on one or both sides of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder.
[0057] According to an embodiment of the present invention, the positive electrode active material includes a high-nickel ternary material.
[0058] According to an embodiment of the present invention, the chemical formula of the high nickel ternary material is Li z Ni x Co y Mn 1-x-y O2, where 0.75≤x≤0.85, 0.075≤y≤0.125, 1.0≤z≤1.1; or the chemical formula is Li z Ni x Co y Al 1-x-y O2, where 0.75≤x≤0.85, 0.075≤y≤0.125, 1.0≤z≤1.1.
[0059] According to an embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one or both sides of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder.
[0060] According to an embodiment of the present invention, the negative electrode active material includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon and soft carbon.
[0061] According to an embodiment of the present invention, the compaction density of the negative electrode sheet is 1.5 to 1.8 g / cm 3 , for example 1.5 g / cm3 , 1.6g / cm 3 , 1.7g / cm 3 or 1.8 g / cm 3 .
[0062] According to an embodiment of the present invention, the average particle size of the negative electrode active material is 13 to 21 μm.
[0063] According to an embodiment of the present invention, the tap density of the negative electrode active material is 0.9 to 1.2 g / cm 3 , for example 0.9 g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 or 1.2g / cm 3 .
[0064] According to an embodiment of the present invention, the hardness of the negative electrode active material is 30 to 60 N / mm 2 , for example 30N / mm 2 、35N / mm 2 , 40N / mm 2 , 45N / mm 2 , 50N / mm 2 , 55N / mm 2 or 60N / mm 2 .
[0065] According to an embodiment of the present invention, the battery satisfies:
[0066] 5.0×10 -3 ≤A / B≤8.0×10 -2 ;
[0067] 1.5≤α≤1.8;
[0068] Wherein, A is the percentage of the mass of the first additive to the total mass of the electrolyte, in wt%; B is the hardness of the negative electrode active material, in N / mm 2 ; α is the compaction density of the negative electrode sheet, in g / cm 3 .
[0069] According to an embodiment of the present invention, A / B is 7.5×10 -3 , 8×10 -3 , 1×10 -2 , 2×10 -2 , 2.5×10 -2 , 3×10 -2 , 3.5×10 -2 , 4×10 -2 , 4.5×10 -2, 5×10 -2 , 6×10 -2 ,7×10 -2 or 8×10 -2 .
[0070] The study found that by adjusting the hardness of the negative electrode active material, the migration path of lithium ions can be adjusted; when the hardness of the negative electrode active material is increased within an appropriate range, this can greatly shorten the migration path of lithium ions, effectively improving the low-temperature performance of the battery while also taking into account the energy density of the battery.
[0071] In particular, when the battery satisfies the following relationship 5.0×10 -3 ≤A / B≤8.0×10 -2 and 1.5≤α≤1.8, the battery dynamics are significantly improved, the low temperature performance of the battery is enhanced and the high energy density characteristics of the battery are taken into account; when the battery does not satisfy the above relationship, the low temperature performance of the battery will deteriorate due to the mismatch between the added amount of the first additive and the negative electrode active material, making it impossible for the battery to have both low temperature performance and high energy density.
[0072] According to an embodiment of the present invention, the mass percentage of each component in the positive electrode active material layer is: 80-99.8wt% of positive electrode active material, 0.1-10wt% of conductive agent, and 0.1-10wt% of binder.
[0073] Preferably, the mass percentage of each component in the positive electrode active material layer is: 90-99.6wt% of positive electrode active material, 0.2-5wt% of conductive agent, and 0.2-5wt% of binder.
[0074] According to an embodiment of the present invention, the mass percentage of each component in the negative electrode active material layer is: 80-99.8wt% of negative electrode active material, 0.1-10wt% of conductive agent, and 0.1-10wt% of binder.
[0075] Preferably, the mass percentage of each component in the negative electrode active material layer is: 90-99.6wt% of negative electrode active material, 0.2-5wt% of conductive agent, and 0.2-5wt% of binder.
[0076] According to an embodiment of the present invention, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder.
[0077] According to an embodiment of the present invention, the binder is selected from at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.
[0078] According to an embodiment of the present invention, the positive electrode of the battery is a high-nickel ternary positive electrode, and the negative electrode of the battery is an artificial graphite negative electrode.
[0079] According to the embodiment of the present invention, when the electrolyte is used in combination with a high-nickel ternary positive electrode-artificial graphite negative electrode, the effect that the electrolyte can achieve can be more prominent. Specifically, since the introduction of additives can reduce the acidity of the electrolyte, this can well avoid the risk of battery gas production caused by high residual alkali on the surface of the high-nickel ternary positive electrode material, and at the same time, the additive can also form a dense interface film at the positive electrode interface that effectively protects and inhibits the destruction of the structure of the high-nickel ternary positive electrode material. The dense interface film on the positive electrode surface can effectively protect the high-nickel ternary positive electrode material from pulverization due to volume expansion / contraction, reduce the dissolution of transition metal nickel elements at high temperatures, and reduce the oxidative decomposition of transition metal nickel ions on the electrolyte; in addition, a protective film rich in Li2SO3 is formed on the negative electrode surface; the interface film formed on the positive and negative electrode surfaces has the characteristics of low impedance, good chemical stability and high high temperature resistance, and the stable and dense positive and negative electrode interface film can also effectively reduce the electrolyte from penetrating into the cracks to react and alleviate capacity decay, which makes the battery well balanced in high and low temperature performance.
[0080] According to an embodiment of the present invention, the charge cut-off voltage of the battery is 4.2V or more.
[0081] Beneficial effects:
[0082] The present invention can significantly improve the performance of the battery by adding a first additive and a second additive to the electrolyte, and the two additives act together on the surface of the positive and negative electrodes. Specifically, the combined use of sulfonylbenzothioxazole compounds and oxazolone compounds can significantly reduce the acidity of the electrolyte, improve the stability of the electrolyte, and ensure the quality of the electrolyte; the sulfonylbenzothioxazole compounds can act on the positive electrode interface to oxidize and form a sulfonic acid lithium salt interface film, which has good high temperature tolerance, avoids direct contact between the positive electrode active material and the electrolyte and stabilizes the microstructure of the positive electrode active material, reduces the dissolution of transition metal nickel elements at high temperatures, and realizes the complexation of transition metal nickel ions, reducing the oxidative decomposition of transition metal nickel ions on the electrolyte. It can significantly improve the high-temperature performance of the battery; oxazolone compounds can act on the negative electrode interface to form a polyoxazolone interface film by ring-opening polymerization. The interface film has good stability, inhibits the reduction reaction of organic solvents at the negative electrode interface, and can also reduce the interface impedance; at the same time, the solid electrolyte membrane formed by the two additives has low impedance, which is beneficial to improving the migration kinetics of lithium ions at the interface, thereby effectively improving the high-temperature storage performance, high-temperature cycle performance, high-temperature floating charge performance and low-temperature discharge performance of lithium-ion batteries.
[0083] The sultone compounds further introduced can participate in the film-forming reaction on the surfaces of the positive and negative electrodes, and can work together with the first additive and the second additive to make the formed solid electrolyte film more stable and have lower impedance, thereby further improving the high-temperature storage performance, cycle performance, high-temperature floating charge performance and low-temperature discharge performance of the obtained battery. DETAILED DESCRIPTION
[0084] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0085] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0086] Preparation method of lithium-ion battery:
[0087] The positive electrode active material high nickel ternary material (NCM811), the binder polyvinylidene fluoride (PVDF), and the conductive carbon black are mixed in a weight ratio of 95:2:3, and N-methylpyrrolidone (NMP) is added, and stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on the current collector aluminum foil; the coated aluminum foil is baked in an oven with 5 different temperature gradients, and then dried in an oven at 120°C for 8 hours, and then rolled and cut to obtain the required positive electrode sheet.
[0088] The negative electrode active material artificial graphite, the binder styrene butadiene rubber, and the conductive agent acetylene black are mixed in a weight ratio of 94:3:3, and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on a high-strength carbon-coated copper foil to obtain a pole piece; the obtained pole piece is dried at room temperature and then transferred to an oven at 80°C for drying for 10 hours, and then rolled and cut to obtain a negative electrode sheet.
[0089] The positive electrode sheet, negative electrode sheet and separator prepared above are stacked in the order of positive electrode sheet, separator PP film and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte is injected into the outer packaging. After vacuum packaging, standing, forming, shaping, sorting and other processes, a lithium-ion battery is obtained.
[0090] Example 1
[0091] This embodiment provides an electrolyte, which includes the following:
[0092] An additive consisting of a first additive of formula I-1 and a second additive of formula II-1;
[0093] The solvent comprises a cyclic carbonate and a chain carbonate, wherein the cyclic carbonate is ethylene carbonate and the chain carbonate is ethyl methyl carbonate;
[0094] The electrolyte salt is LiPF6;
[0095] Among them, the mass ratio of the cyclic carbonate to the chain carbonate is 1:2.5; the molar concentration of the electrolyte salt in the mixed solvent formed by the cyclic carbonate and the chain carbonate is 1.2 mol / L; the mass of the first additive is 0.3% of the total mass of the electrolyte; and the mass of the second additive is 1.2% of the total mass of the electrolyte.
[0096] Preparation method: The cyclic carbonate, chain carbonate, electrolyte salt, first additive and second additive are stirred and mixed at 25° C. to obtain the electrolyte.
[0097] Examples 2-33 and Comparative Examples 1-6
[0098] The electrolytes of Examples 2-33 and Comparative Examples 1-6 are the same as those of Example 1, except that the types and contents of the additives in the electrolytes are different, as shown in Table 1.
[0099] Examples 34-35
[0100] The electrolytes of Examples 34-35 are the same as those of Example 17, except that the compaction densities of the negative electrode sheets are different, as shown in Table 1.
[0101] Embodiment 36
[0102] The electrolyte of Example 36 is the same as that of Example 17, except that the hardness of the negative electrode active material is different, as shown in Table 1.
[0103] Table 1 Composition of lithium ion batteries of embodiments and comparative examples
[0104]
[0105]
[0106] Electrochemical performance test: The electrochemical performance test is carried out using the following test methods using a Blue Electric charge and discharge test cabinet:
[0107] (1) High temperature cycle performance test
[0108] High temperature cycle performance test: At 45°C, the divided battery is charged to 4.2V at 1C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 2.8V at 1C constant current. After 500 cycles of charge and discharge, the capacity retention rate at the 500th week is calculated. The calculation formula is as follows:
[0109] The 500th cycle capacity retention rate (%) = (500th cycle discharge capacity / first cycle discharge capacity) × 100%.
[0110] (2) Low temperature discharge performance test
[0111] Under 25℃ environmental conditions, discharge the divided battery at 1C to 2.8V and set aside for 5min; then charge it at 1C to 4.2V. When the cell voltage reaches 4.2V, change to 4.2V constant voltage charging until the charging current is less than or equal to the given cutoff current 0.05C and set aside for 5min; transfer the fully charged cell to a high and low temperature box, set to -20℃, and set aside for 120min after the temperature of the box is reached; then discharge it at 1C to a termination voltage of 2.8V and set aside for 5min; then adjust the temperature of the high and low temperature box to 25℃±3℃, and set aside for 60min after the box temperature is reached; charge it at 1C to 4.2V. When the cell voltage reaches 4.2V, change to 4.2V constant voltage charging until the charging current is less than or equal to the given cutoff current 0.05C; set aside for 5min; calculate the -20℃ low temperature discharge 2.8V capacity retention rate. The calculation formula is as follows:
[0112] -20℃ discharge to 2.8V capacity retention rate (%) = (-20℃ discharge to 2.8V discharge capacity / 25℃ discharge to 2.8V discharge capacity) × 100%.
[0113] (3) 60℃, 30 days high temperature storage test
[0114] The battery was placed at room temperature and charged and discharged once at 1C (4.2V-2.8V), and the discharge capacity C0 of the battery before storage was recorded. Then the battery was charged to a full charge state of 4.2V with constant current and constant voltage. The thickness d1 of the battery before high-temperature storage was tested with a vernier caliper (the two diagonals of the above battery were connected by a straight line, and the intersection of the two diagonals was the battery thickness test point). The battery was placed in a 60°C constant temperature box and stored for 30 days. After the storage was completed, the battery was taken out and the thermal thickness d2 of the battery after storage was tested. The battery thickness expansion rate after storage at 60°C for 30 days was calculated. After the battery was cooled at room temperature for 24 hours, the battery was again discharged to 2.8V with 1C constant current and constant voltage, and then charged to 4.2V with 1C constant current and constant voltage. The discharge capacity C1 and charge capacity C2 of the battery after storage were recorded, and the capacity remaining rate and recovery rate of the battery after storage at 60°C for 30 days were calculated. The calculation formula is as follows:
[0115] Thickness expansion rate after storage at 60°C for 30 days = (d2-d1) / d1*100%;
[0116] Residual capacity retention after storage at 60°C for 30 days = C1 / C0*100%;
[0117] After storage at 60°C for 30 days, the recovery capacity retention rate = C2 / C0*100%.
[0118] (4) Float charge at 45℃ for 100 hours
[0119] In an environment of (25±2)℃, discharge at 1C constant current to a cut-off voltage of 2.8V, leave for 5 minutes, charge at 1C constant current and constant voltage to a cut-off voltage of 4.2V, and a cut-off current of 0.05C, and test the cell thickness T0; place the cell in an environment of (45±2)℃ and let it stand for 4 hours to reach thermal equilibrium. In an environment of (45±2)℃, charge at 1C constant current to 4.2V and keep the constant voltage at 4.2V for 100 hours. Take out the cell and place it in an environment of (25±2)℃ and let it stand for 4 hours to reach thermal equilibrium. In an environment of (25±2)℃, discharge at 1C constant current to a cut-off voltage of (2.8V), leave for 5 minutes, charge at 1C constant current and constant voltage to a cut-off voltage of 4.2V, and a cut-off current of 0.05C, and test the cell thickness T1.
[0120] Thickness change rate after 100 hours of floating charge at 45℃=(T1-T0) / T0*100%
[0121] Table 2 Performance test results of lithium ion batteries of the embodiments and comparative examples
[0122]
[0123]
[0124] From the test results in Table 2, it can be seen that the electrolyte of the embodiment effectively improves the high-temperature storage performance, high-temperature cycle performance, high-temperature floating charge performance and low-temperature discharge performance of the lithium-ion battery compared with the electrolyte of the comparative example.
[0125] Specifically, from the comparison of Examples 1-17, it can be seen that when the specific structures of the first additive and the second additive are adjusted, the high temperature storage performance, high temperature cycle performance, high temperature floating charge performance and low temperature discharge performance of the battery can be improved, among which the improvement effect of Example 2 is the most prominent.
[0126] From the comparison of Examples 1 and 18-23, it can be seen that the content of sulfonylbenzothioxazole compounds will affect the high-temperature storage performance, high-temperature cycle performance, high-temperature floating charge performance and low-temperature discharge performance of the battery. When the content of sulfonylbenzothioxazole compounds increases, the film-forming impedance will be too large, the first efficiency and capacity of the battery will be low, and the high and low temperature performance of the battery will decrease; when the sulfonylbenzothioxazole compounds decrease, the acid removal, water removal and film-forming effects will be poor, which will also lead to a decrease in the high and low temperature performance of the battery. When the content of sulfonylbenzothioxazole compounds is in the range of 0.02-5wt%, good high and low temperature performance of the battery can be obtained, especially when the content of sulfonylbenzothioxazole compounds is in the range of 0.05-3wt%, the performance of the obtained battery is more outstanding.
[0127] From the comparison of Examples 1, 24-28, it can be seen that the content of oxazolone compounds will affect the high-temperature storage performance, high-temperature cycle performance, high-temperature floating charge performance and low-temperature discharge performance of the battery. When the amount of oxazolone compounds added increases, the battery impedance will be too large, the first effect and capacity will be reduced, the rate and low-temperature performance will decrease, and the gas production will increase during high-temperature storage, thereby increasing the volume expansion rate of the battery; when the amount of oxazolone compounds added decreases, the film-forming effect on the surface of the high-nickel positive electrode and the surface of the artificial graphite negative electrode will be poor, resulting in a decrease in the high-temperature cycle performance and high-temperature storage performance of the battery. When the content of oxazolone compounds is in the range of 0.1-8wt%, good high and low temperature performance of the battery can be obtained, especially when the content of oxazolone compounds is in the range of 0.2-5wt%, the performance of the obtained battery is more outstanding.
[0128] From the comparison of Examples 29-33, it can be seen that adding a sultone compound on the basis of Example 1 can improve the high and low temperature performance of the battery, especially the high temperature floating charge performance of the battery.
[0129] When the content of the sultone compound is in the range of 0.1-10 wt %, good battery performance improvement can be obtained, and especially when the content of the sultone compound is in the range of 1-3.5 wt %, the performance of the obtained battery is more outstanding.
[0130] From the comparison of Examples 17-23 and 34-36, it can be seen that when the battery meets the 5.0×10 -3 ≤A / B≤8.0×10 -2 When α≤1.8 and 1.5≤α≤1.8, the battery dynamics are significantly improved, the low temperature performance of the battery is enhanced and the high energy density characteristics of the battery are taken into account; when the battery does not satisfy the above relationship, the low temperature performance of the battery deteriorates due to the mismatch between the amount of additive added and the negative electrode active material, making it impossible for the battery to have both low temperature performance and high energy density.
[0131] From the comparison of Example 1 and Comparative Examples 1-5, it can be seen that when the electrolyte is added with sulfonylbenzothioxazole compounds and oxazolone compounds at the same time, the combination of the two achieves a synergistic effect, which can effectively improve the high-temperature storage performance, high-temperature cycle performance, high-temperature floating performance and low-temperature discharge performance of the lithium-ion battery. In particular, further introducing sultone compounds on the basis of sulfonylbenzothioxazole compounds and oxazolone compounds can significantly improve the high-temperature storage performance, high-temperature cycle performance, high-temperature floating performance and low-temperature discharge performance of the lithium-ion battery. From the above test results, it can be seen that the combination of three different types of additives can significantly improve the performance of the battery.
[0132] From the comparison between Example 1 and Comparative Example 6, it can be seen that the sulfonylbenzothioxazole compounds of the present application can achieve a synergistic effect when used in combination with oxazolone compounds, while the sulfonylpyridine compounds (or other sulfonyl heterocyclic compounds) cannot achieve a synergistic effect when used in combination with oxazolone compounds.
[0133] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: The electrolyte includes an organic solvent, an electrolyte salt, a first additive and a second additive; the first additive includes a sulfonylbenzothioxazole compound, and the second additive includes an oxazolone compound.
2. The electrolyte according to claim 1, characterized in that The sulfonylbenzothioxazole compound includes at least one of the compounds shown in Formula I: Wherein, R1 is selected from hydrogen, halogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkoxy; if substituted, the substituent is alkyl or halogen; R2 is selected from halogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkoxy, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl; if substituted, the substituent is alkyl or halogen; Y is O element or S element. Preferably, R1 is selected from halogen, substituted or unsubstituted C 1-12 Alkyl, substituted or unsubstituted C 1-12 Alkoxy; if substituted, the substituent is C 1-12 Alkyl or halogen; R2 is selected from halogen, substituted or unsubstituted C 1-12 Alkyl, substituted or unsubstituted C 2-12 Alkenyl, substituted or unsubstituted C 1-12 Alkoxy, substituted or unsubstituted C 6-12 aryl, substituted or unsubstituted 5-12 membered heteroaryl; if substituted, the substituent is C 1-12 Alkyl or halogen; Y is O element or S element. Preferably, the first additive comprises at least one of the following compounds I-1 to I-11:
3. The electrolyte according to claim 1 or 2, characterized in that The mass of the first additive accounts for 0.02 wt% to 5 wt% of the total mass of the electrolyte, and preferably 0.05 to 3 wt%.
4. The electrolyte according to claim 1, characterized in that The second additive comprises at least one of the compounds of formula II: Wherein, R3 is selected from substituted or unsubstituted alkyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl; if substituted, the substituent is alkoxy, alkyl or halogen. Preferably, R3 is selected from substituted or unsubstituted C 1-12 Alkyl, substituted or unsubstituted C 6-12 aryl, substituted or unsubstituted 5-12 membered heteroaryl; if substituted, the substituent is C 1-12 Alkoxy, C 1-12 Alkyl or halogen. Preferably, the second additive comprises at least one of the following compounds II-1 to II-7:
5. The electrolyte according to any one of claims 1 to 4, characterized in that The mass percentage of the second additive to the total mass of the electrolyte is 0.1wt% to 8wt%, preferably 0.2wt% to 5wt%.
6. The electrolyte according to any one of claims 1 to 5, characterized in that: The electrolyte includes a third additive, and the third additive includes a sultone compound. Preferably, the sultone compound comprises at least one of the compounds represented by formula III: Wherein, R4, R5, and R6 are the same or different and are independently selected from hydrogen, halogen, substituted or unsubstituted alkyl; if substituted, the substituent is alkyl or halogen. Preferably, R4, R5, R6 are the same or different and are independently selected from hydrogen, halogen, substituted or unsubstituted C 1-12 Alkyl; if substituted, the substituent is C 1-12 Alkyl or halogen. Preferably, the sultone compound is selected from at least one of the following compounds III-1 to III-10:
7. The electrolyte according to claim 6, characterized in that The mass percentage of the third additive to the total mass of the electrolyte is 0.1 wt% to 10 wt%, preferably 1.0 wt% to 3.5 wt%.
8. A battery comprising the electrolyte according to any one of claims 1 to 7.
9. The battery according to claim 8, characterized in that The battery further comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material comprises a high-nickel ternary material. Preferably, the chemical formula of the high nickel ternary material is Li z Ni x Co y Mn 1-x-y O2, where 0.75≤x≤0.85, 0.075≤y≤0.125, 1.0≤z≤1.1; or the chemical formula is Li z Ni x Co y Al 1-x-y O2, where 0.75≤x≤0.85, 0.075≤y≤0.125, 1.0≤z≤1.
1.
10. The battery according to claim 8 or 9, characterized in that: The battery meets the following requirements: 5.0×10 -3 ≤A / B≤8.0×10 -2 ; 1.5≤α≤1.8; Wherein, A is the percentage of the mass of the first additive to the total mass of the electrolyte, in wt%; B is the hardness of the negative electrode active material, in N / mm 2 ; α is the compaction density of the negative electrode sheet, in g / cm 3 .
Citation Information
Patent Citations
Non-aqueous electrolyte, power battery containing non-aqueous electrolyte and vehicle containing power battery
CN110400968A
Dioxazolones and nitrile sulfites as electrolyte additives for lithium-ion batteries
CN112514131A
Non-aqueous electrolyte and lithium ion battery containing the non-aqueous electrolyte
CN113823837A
Electrolyte additive, electrolyte containing electrolyte additive, lithium ion secondary battery and application of electrolyte additive
CN115706262A
Lithium ion battery
CN116845370A